Implementasi Flashcard 3d Berbasis Augmented Reality Sebagai Media Pendukung Pembelajaran Klasifikasi Hewan Pada Anak Usia Dini - Maulana Sihdi Habibie; Nisa Atthalia; Fahri Fahri; Ahmad Thoriq Alqi Ighafur; Aqib Ainun Najib; Muhammad Zainudin Al Amin; Achmad Solichan; Basirudin Ansor; Nova Christina Sari; Aditya Putra Ramdani (Jurnal Teknologi informasi dan Ilmu Komputer, 2026)
An Augmented Reality (AR)-based learning application was developed as an interactive visual medium to introduce animal classification to early childhood learners. The application uses flashcards scanned with a device camera to display three-dimensional (3D) objects in real time. This study aims to design and build an AR-based mobile application using Unity and Vuforia as an engaging self-learning tool. Development followed the Multimedia Development Life Cycle (MDLC), comprising concept, design, material collection, assembly, testing, and distribution. Functional black-box testing across 12 scenarios showed a 100% success rate, with all features operating as designed, including menu navigation, marker scanning, and 3D object visualization. Preliminary observations indicated that the visualization increased children's interest and involvement during learning, although this effect has not yet been measured with a validated evaluation instrument. Therefore, the application is considered a practical interactive medium for introducing animal classification based on feeding type - carnivores, herbivores, and omnivores - to young children.